Mediação docente e tecnologia digital de informação e comunicação na perspectiva da educação inclusiva - Souza, Evaneyde dos Santos (2024)
The impact of Digital Information and Communication Technologies (DICT) in different social contexts, and precisely in the educational context, has converged towards new perspectives on the teaching and learning process, which is marked by the challenge of integrating DICT into teaching practices, as well as due to the need to respond to an increasingly heterogeneous classroom reality, especially based on educational inclusion policies. We understand that teaching mediation involves possibilities for articulating resources, needs and educational intentions. Given this scenario, this thesis aimed to understand teaching methodological strategies in the process of integrating TDIC from an inclusive perspective. The research, with a qualitative approach, integrates the studies developed by the Communication and Technology Research Center (NUCA) and was developed on the São Cristóvão campus of the Federal Institute of Sergipe and, through the case study method, sought to relate data from three groups of participants: teachers, students in inclusion situations and a multidisciplinary team using questionnaire, interview, document analysis and classroom observation instruments, which were interpreted from the analysis perspective of Bardin (2016). The research data showed that the researched context goes through the different stages of integration of TDIC through practices that demonstrated didactic mediation, including accessibility parameters. The perception of inclusion conflicts between discourses of adaptation versus inclusion and lack of initial and continuing training. Possibilities for teaching learning in the educational environment and through collaborative work were highlighted.